Assessing Digital Maturity in Healthcare: A Case Study of Jember Klinik Hospital, Indonesia - Aviati, Kurnia; Kudus, Kudus; Putra, Dewa Ngakan Gde Wahyu Mahatma; Naya, Aulia Riswanti (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to assess the digital maturity level of Jember Klinik Hospital, a private healthcare facility in Indonesia, using a structured evaluation framework. A descriptive cross-sectional design was employed in June 2024, involving six internal stakeholders representing IT, medical, nursing, and administrative leadership. Data were collected using the Digital Maturity Level Assessment Tool (Version 1.1) developed by the Indonesian Ministry of Health, consisting of 38 parameters across seven domains. The assessment was conducted collaboratively through structured meetings, document reviews, and consensus-based scoring. Descriptive analysis revealed that the hospital has reached an advanced level of digital maturity. The highest scores were found in Standards and Interoperability (4.8) and Governance and IT Management (4.8), reflecting strong planning and regulatory alignment. Electronic Medical Records and Patient-Centered Care also scored highly (4.7), indicating effective digital integration in clinical workflows. However, Data Analytics received the lowest score (2.8), pointing to significant gaps in data quality and analytical capacity. These findings suggest the need for enhanced investment in data infrastructure, staff training, and interoperability improvements. The results contribute to understanding digital health readiness in Indonesia’s private healthcare sector and provide actionable insights for supporting targeted digital transformation strategies.